Addressing issues in the mental health system from the perspective of law and system from the perspective of law and maqasid shariah - Safuan, Sahida; Abdul Ghani Azmi, Ida Madieha (2021)
Malaysia's mental health care system was already in rough condition before the Covid-19 pandemic, and the situation has only worsened since then. According to the National Health and Morbidity Survey 2015, the prevalence of mental health problems among adults has risen steadily from 10.7% in 1996 to 29.2% in 2015 with females, younger adults, and those from low-income families seeing greater rates. It means that 1 out of 3 adults in Malaysia struggling with mental health issues. When it comes to mental illness, stigma and discrimination are the two major obstacles. The mental healthcare services which are frequently underequipped to cope with mental health problems is also another issue that requires immediate attention. Both issues should have been a strong impetus for the government to adopt reforms in terms of laws and public policy that can effectively tackle the mental health problem. This paper attempts to enhance the mental health legislations and policies by looking into the perspective of maqasid shariah. The harmonization of the current mental health framework with maqasid-based framework for mental health legal policy is supposed to guide policymakers toward a better legislative framework that prioritises the individual's well-being while lowering risk and harm to society.